Challenging The Form of Responsibility in Drug Policies That Adversely Affect Consumers: Causality Theory As An Analytical Lens - Yuyut Prayuti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
It becomes a real polemic when a drug intended for health development to support national development actually becomes a serious threat to health itself. The purpose of this study is to answer the issue of responsibility for drugs that cause adverse effects on consumers. This research uses normative juridical method. In this research, it is found that the constitution has massively regulated the relationship that implies responsibility in terms of drugs that cause adverse effects to consumers. Based on the theory of causality, in addition to pharmaceutical companies that can be charged with absolute liability in accordance with the provisions of Article 19 of the Consumer Protection Law, the Food and Drug Supervisory Agency (BPOM) can also be blamed, especially if the elements of abuse of duty and negligence are met based on Presidential Regulation No. 80 of 2017 concerning BPOM.